Kepemimpinan Kepala Sekolah - Kurniati (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2021)
The existence of leaders is needed in an organization, this is because leaders who will determine the direction of the organization will be brought to where. Leadership itself is a person's activity in influencing and moving all its members to be able to achieve the stated goals. leadership is understood as the power to move and influence people. The leader in the educational institution is the principal. the principal must be able to mobilize all citizens of the school to achieve educational goals. Educational leadership is carried out at educational institutions, with the aim of influencing all school citizens to carry out their duties and work properly and correctly in accordance with their respective responsibilities which ultimately aims to develop all the potential possessed by students.